2013
DOI: 10.1186/1746-6148-9-76
|View full text |Cite
|
Sign up to set email alerts
|

Within-host evolution of Brucella canis during a canine brucellosis outbreak in a kennel

Abstract: BackgroundLittle is currently known about Brucella evolution within the host during infection. The current study is the first to employ fine-scale genotyping on an isolate collection derived from a Brucella canis outbreak. Eight isolates of B. canis, cultured from different tissues of three dogs (female, stud dog, puppy of another female) from a single kennel over three months were genetically characterized with a 15-marker multi-locus, variable-number tandem repeat (VNTR) analysis (MLVA) to assess the genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 23 publications
1
10
0
1
Order By: Relevance
“…Also, within the Brucella genus, a study reporting on an outbreak of B . canis at a Hungarian dog kennel, noted that high mutation rates of some MLVA loci within animals presented a difficulty in unambiguously inferring epidemiological relationships between animals [ 38 ]. Similar findings with hypervariable loci affecting precision have been noted in cattle [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, within the Brucella genus, a study reporting on an outbreak of B . canis at a Hungarian dog kennel, noted that high mutation rates of some MLVA loci within animals presented a difficulty in unambiguously inferring epidemiological relationships between animals [ 38 ]. Similar findings with hypervariable loci affecting precision have been noted in cattle [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in Brucella have reported variation of SNPs among isolates recovered from the same host tissues or among isolates obtained from the same host sampled at different times. A study of a B. canis outbreak in Hungary reported variation in five of 15 different VNTR alleles at multiple tissues and dates, during three months, suggesting rapid genetic changes in B. canis that produced the emergence of alternative alleles at the VNTR loci [ 169 ]. Another example using MLVA is provided by Maquart et al (2009) in marine Brucella : they cultured and typified bacteria from more than one tissue in 69 marine mammals, and they observed more than one genotype in sixteen of them.…”
Section: Microevolution Of Brucella In the Hostmentioning
confidence: 99%
“…), (iii) within‐host evolution of the bacteria (Gyuranecz et al. ), or (iv) changes in bacteria population through time (for viruses, see: Volz et al. ; Frost and Volz ).…”
Section: Discussionmentioning
confidence: 99%